Dealing with cost-push inflation in Latin America: Multi-causality in a context of increased openness and commodity price volatility - Abeles, Martin (2015)
Despite recognizing the exogenous, cost-push nature of recent inflationary pressures in Latin America, plus the difficulties faced by monetary authorities in dealing, under such circumstances, with internal and external disequilibria simultaneously, intellectual attention in policy circles remains focused on demand-side issues and policy instruments. This paper develops an eclectic model that has the potential to nest demand-side elements, but focuses on cost-push factors - distributional conflict and propagation mechanisms - as typically addressed by the post-Keynesian-structuralist tradition. In addition to shedding some light on the nature of inflationary pressures as experienced in Latin American countries during the recent commodity boom - in particular South American commodity exporting economies - the paper’s main goal is to portray the policy and instrumental trade-offs faced by policy-makers themselves. By bringing unconventional policy devices into the model (such as direct interventions in commodity markets), we hope to broaden the scope of the conventional macroeconomic policy instruments.